2016
DOI: 10.3390/healthcare4030069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Flavonoids on Oxidative Stress and Inflammation in Adults at Risk of Cardiovascular Disease: A Systematic Review

Abstract: Oxidative stress (OS) and inflammatory processes initiate the first stage of cardiovascular disease (CVD). Flavonoid consumption has been related to significantly improved flow-mediated dilation and blood pressure. Antioxidant and anti-inflammatory mechanisms are thought to be involved. The effect of flavonoids on markers of oxidative stress and inflammation, in at risk individuals is yet to be reviewed. Systematic literature searches were conducted in MEDLINE, Cochrane Library, CINAHL and SCOPUS databases. Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 35 publications
(83 reference statements)
0
39
0
Order By: Relevance
“…Since NO degradation is mediated by free radicals, the improvement in vascular function is also related to the anti-inflammatory and antioxidant properties of cocoa ( 88 ). In a systematic review of the literature on polyphenols and oxidative stress, four studies reported statistically significant improvements in markers of oxidative stress and inflammation after flavanol-rich cocoa intake ( 89 ). A significant reduction in oxidative stress occurred when dark chocolate was administered to smokers as opposed to milk chocolate ( 90 ).…”
Section: Putative Mechanismsmentioning
confidence: 99%
“…Since NO degradation is mediated by free radicals, the improvement in vascular function is also related to the anti-inflammatory and antioxidant properties of cocoa ( 88 ). In a systematic review of the literature on polyphenols and oxidative stress, four studies reported statistically significant improvements in markers of oxidative stress and inflammation after flavanol-rich cocoa intake ( 89 ). A significant reduction in oxidative stress occurred when dark chocolate was administered to smokers as opposed to milk chocolate ( 90 ).…”
Section: Putative Mechanismsmentioning
confidence: 99%
“…Included and excluded participants did not differ according to sex, age, parental education, alcohol consumption, and smoking status. More of the included participants were from non-Mediterranean countries, had a higher pubertal stage (more Tanner stage 3), had a higher material condition in the family [high Family Affluence Scale (FAS) score (5)(6)(7)(8), which was based on adolescents' report on Internet availability at home (0, no; 1, yes), family car ownership (0-3, depending on amount), computer ownership (0-3, depending on amount), and having one's own bedroom (0, no; 1, yes)], and more often had an optimal BMI.…”
Section: Study Populationmentioning
confidence: 99%
“…In recent years, many studies have underlined the potential health benefit of dietary polyphenols as anti-inflammatory effects on atherosclerosis, type 2 diabetes, cancer, and mortality (2)(3)(4)(5)(6). Further research is needed since 1 meta-analysis showed mostly nonlinear associations in the prevention of type 2 diabetes (7) and a systematic review detected inconsistent effects of flavonoid consumption towards inflammation depending on polyphenol source and type of high-risk populations (8). Indeed, only certain polyphenol classes and individual polyphenols abundant in specific foods showed anti-inflammatory effects: for example, cocoa flavonoids showed anti-inflammatory effects in type 2 diabetics and olive oil phenolic compounds in mildly hypertensive women (8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The failure of antioxidants found in foods, such as vitamins C and E, to prevent these disorders has led to the exploration of the ROS-suppressive effects of drugs used in the treatment of cardiovascular disease [ 6 , 7 ]. Moreover, many natural products have antioxidant and various other pharmacological properties [ 8 ]. Some of their actions on oxidative stress are associated with pharmacological effects [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%